Predicting Neoadjuvant Chemotherapy in Nonconcentric Shrinkage Pattern of Breast Cancer Using 1H-Magnetic Resonance Spectroscopic Imaging. Issue 1 (January 2018) - Zhou, Juan; Qiao, Peng-Gang; Zhang, Hong-Tao; Li, Gong-Jie; Jiang, Ze-Fei
Abstract : Objective: The aim of this study was to explore the response to neoadjuvant chemotherapy (NAC) in nonconcentric shrinkage pattern of breast cancer (BC) patients using 1 H–magnetic resonance spectroscopy. Methods: Twenty-five BC patients were the study cohort. All patients received AT-based regimen as first-line treatment. Tumor response to chemotherapy was evaluated after the second and fourth cycles using magnetic resonance imaging and magnetic resonance spectroscopy. Final histopathology following surgery after 4 to 8 cycles of NAC served as a reference. Changes in total choline integral* (tCho) and tumor size in response versus nonresponse groups were compared using the 2-way Mann-Whitney nonparametric test. Receiver operating characteristic (ROC) analyses were undertaken, and the area under the ROC curve compared among them. Results: 1 H–magnetic resonance spectroscopy revealed a negative tCho integral* in 6 cases at the first follow-up and 14 cases at the second follow-up. Based on pathology (Miller-Payne system), there were 16 cases of response, and 9 cases of nonresponse. The tCho integral* was significantly different between the response and nonresponse groups at the second follow-up ( P = 0.027). The tumor size changes were not significantly different in the response and nonresponse groups at the second follow-up study ( P > 0.05). The comparison of ROC curves among the change in tCho integral* and tumor size at baseline and both follow-ups revealed the maximum area under the ROC curve of the change in tCho integral* to be 0.747 at the second follow-up, sensitivity to be 93.75%, and positive predictive value to be 78.9%. Conclusions: In nonconcentric shrinkage pattern after NAC of BC, when tumor size is difficult to reflect the response, tCho integral* reduction may be a predictive marker.